Factors influencing on obtaining a light output homogeneous distribution along long-length detectors based on CsI(Tl) scintillators - Zosim, D.I. (Functional Materials, 2018)
The role of matting the long-dimension scintillators based on CsI(Tl) single crystals for achieving a homogeneous distribution of light output along their length was studied. It was shown that he matting of scintillators resulted in developing roughness on their surface and in violating the optical homogeneity which is manifested in the appearance of birefringence bands. It is established that the maximum homogeneity of the distribution of the light output along long-length detectors is achieved due to the interaction of the light of scintillations with the regions of the crystal in which the optical characteristics differ from those in the neighboring space with these regions.